ESTUDO DA SUBSTITUIÇÃO DE TITÂNIO POR ESTANHO EM SISTEMA SnXTi1-XO2 - Berger, Danielle (2009)
A study about the mixing system of SnO2 and TiO2 oxides was performed by using different experimental methods and theoretical calculation. Selected compositions in the SnxTi1-xO2 system (where x = 0, 0.25, 0.50, 0.75, 1) were calcined at different temperatures (500C, 700C, 800C, 950C and 1200C) and analyzed by various techniques. In these temperatures, only structures of the cassiterite and the rutile phase without solid solution formation of the SnxTi1-xO2 system were founded by experimental methods, according to X-ray diffraction results. However, the formation of this solid solution from a single phase of rutile was indicated by results of theoretical calculation. The stoichiometric composition of oxides in the SnxTi1-xO2 system was determined by X-ray fluorescence. Photodegradation of rhodamine B catalyzed by samples of SnO2, TiO2 and SnxTi1-xO2 shown better results when compared to the pure rhodamine B. Results of isoelectrical potential helps to understanding how each particle surface can react during the catalysis of the photodegradation process. In addition, theoretical results explain the behaviour of the studied materials. According to these results, the existence of several possible states for recombination between electron-hole pair during electron excitation and decay can be predicted in the catalyzed photodegradation.